THE Actualization Of Religious Moderation Values In SD Darut Thalabah Wonosari - Wafi, Ali; Washil, Sobri; Serinio, Foad (AL MURABBI, 2023)
The purpose of this study is to reveal the actualization of religious moderation values carried out through the application of religious education by integrating multicultural education at Darut Thalabah Wonosari Elementary School. SD Darut Thalabah itself is one of the Islamic education models that has heterogeneous students, both in terms of ethnicity and ethnicity so that so far it has instilled moderate character into something interesting to be revealed in this research. This approach is a qualitative type of case study, using interviews, observation and documentation to explore data and then the data is analyzed using an interactive model. The results of this study are The results showed that the values of religious moderation at SD Darut Tholabah have been well implemented through routine habits carried out by the school so that through these habits it can form the character of students who are tolerant and can appreciate the differences that exist.